Rekonstruksi Pembelajaran Istima’ melalui Media Audio-Visual: Studi Efektivitas pada Pembelajar Bahasa Arab di Markaz Arabiyyah Al-Ittifaqiah Indralaya - Andini Andini; Ahmad Tarmizi; Jamanuddin Jamanuddin (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Twenty-first century education demands innovative learning approaches that can enhance fundamental language skills, including istimā‘ (listening), which is an essential receptive skill in Arabic language learning. The use of audio-visual media based on local wisdom serves as a relevant alternative because it provides authentic, engaging, and easily understandable learning contexts. This study aims to determine the effectiveness of using audio-visual media based on local wisdom videos in improving students’ istimā‘ skills at Markaz Arabiyyah Al-Ittifaqiah Indralaya. This research employed a quantitative method with a pre-experimental one-group pretest–posttest design. Data were collected through listening skill tests administered before and after the treatment. The findings indicate a significant improvement, where the average pretest score of 50.13, categorized as low, increased to 81.93, categorized as high, after the implementation of the media. Statistical analysis using the paired sample t-test showed a significance value of < 0.05, confirming a significant difference between the two scores. The N-Gain calculation also indicated medium to high improvement. These results demonstrate that audio-visual media based on local wisdom is effective in istimā‘ learning, as it helps students better understand meaning, intonation, and contextual cues in the Arabic language.